2015
DOI: 10.1039/c4cs00311j
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of secondary and tertiary phosphine oxides to phosphines

Abstract: Achiral or chiral phosphines are widely used in two main domains: ligands in organometallic catalysis and organocatalysis. For this reason, the obtention of optically pure phosphine has always been challenging in the development of asymmetric catalysis. The simplest method to obtain phosphines is the reduction of phosphine oxides. The essential difficulty is the strength of the P=O bond which involves new procedures to maintain a high chemio- and stereoselectivity. The reduction can occur with retention or inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
152
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(154 citation statements)
references
References 106 publications
1
152
0
1
Order By: Relevance
“…[1] Reduction of stable phosphine(V) oxides remains the most straightforward preparation of phosphines, and is often essential for the construction of easily-oxidized electron-rich phosphines. [3] Unfortunately, current methods are extremely harsh, which limits the substrate scope and precludes reaction telescoping. [4] …”
mentioning
confidence: 99%
“…[1] Reduction of stable phosphine(V) oxides remains the most straightforward preparation of phosphines, and is often essential for the construction of easily-oxidized electron-rich phosphines. [3] Unfortunately, current methods are extremely harsh, which limits the substrate scope and precludes reaction telescoping. [4] …”
mentioning
confidence: 99%
“…Secondly, atom efficiency has also been a concern, and improvements in this regard have recently gained increasing attention. The two basic approaches here are the recovery of the initial phosphine by reductive methods [22], which often requires hazardous reagents and is not always efficient or the direct re-use of the phosphine oxides as reagents or catalysts [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Using more reactive silanes proved to be beneficial and excellent conversions and yields were obtained by the group of Werner using hexyl silane as the reducing agent and triflic acid as the catalyst [17]. The most commonly used reductants for P=O bonds include silanes, boranes and metal hydrides based on Al and Ca [7]. Among silanes, as early as 1964, Fritzsche, et al [8][9][10] reported that phenylsilane, diphenylsilane, triphenylsilane and PMHS (polymethylhydrosiloxane, Scheme 1) could be used in excess stoichiometry to reduce alkyl, aryl phosphine oxides and dihydrophosphole oxides (Scheme 2).…”
Section: Scheme 1 General Structure Of Pmhs (Polymethylhydrosiloxane)mentioning
confidence: 99%
“…The most commonly used reductants for P=O bonds include silanes, boranes and metal hydrides based on Al and Ca [7]. Among silanes, as early as 1964, Fritzsche, et al [8][9][10] reported that phenylsilane, diphenylsilane, triphenylsilane and PMHS (polymethylhydrosiloxane, Scheme 1) could be used in excess stoichiometry to reduce alkyl, aryl phosphine oxides and dihydrophosphole oxides (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation